Prevention of Infections in Cardiac Surgery (PICS)-Prevena Study – A pilot/vanguard factorial cluster cross-over RCT - Thomas C. Scheier; Richard Whitlock; Mark Loeb; Philip James Devereaux; Andre Lamy; Michael McGillion; MacKenzie Quantz; Ingrid Copland; Shun-Fu Lee; Dominik Mertz (PLoS ONE, 2025)
Sternal surgical site infections after cardiac surgery can lead to significant morbidity, mortality, and cost. The effects of negative pressure wound management and adding vancomycin as perioperative antimicrobial prophylaxis are unknown. The PICS-PREVENA pilot/vanguard trial, a 2x2 factorial, open label, cluster-randomized crossover trial with 4 periods, was conducted at two major cardiac surgery hospitals in Ontario, Canada. Sites were randomized to one of eight sequences of the four study arms (Cefazolin or Cefazolin + Vancomycin (not analyzed) and standard wound dressing or a negative pressure 3M Prevena incision management system (Prevena). Only diabetic or obese patients were eligible for the latter comparison. This trial investigated feasability including adherence to protocol of each intervention (goal: > 90% each) and loss to follow-up (goal: < 10%). Among the 4107 included patients, 2230 were obese/diabetic (1208 standard wound dressing period, 1022 during Prevena period). Compliance to wound management and antimicrobial prophylaxis was 68.1% and 98.7%, respectively. Loss to follow-up was 3.6%. Deep/organ-space sternal surgical site infections occurred in 16 (1.6%) patients in the Prevena allocated periods and in 17 (1.4%) patients in the standard wound dressing allocated periods (OR= 1.11, 95% CI: 0.56–2.20). Other clinical outcomes did not suggest a difference and a post-hoc as-treated analysis showed similar results. This study showed challenges with introducing a novel technology as standard of care, with non-compliance mostly driven by one of the sites. No firm conclusions should be drawn regarding the effectiveness of Prevena, as this vanguard trial was not powered for clinical outcomes.